Strengthening the targeting performance of a child nutrition-oriented safety net in Bangladesh: the Improved Maternity and Lactating Mother Allowance - CGIAR Research Program on Policies, Institutions, and Markets (2018)
Upon request of the Ministry of Women and Children Affairs of Bangladesh, IFPRI/PIM proposed eligibility criteria to strengthen the targeting performance of the Improved Maternity and Lactating Mother Allowance program in Bangladesh. The government accepted IFPRI's recommendations, which are anticipated to benefit approximately 700,000 poor rural and 250,000 poor urban women in 2018-2019.